PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN VIDEO ANIMASI TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV UPT SDN NO. 78 BALANG KABUPATEN TAKALAR - Ayuni, Dea; Rahmawati; Aeni Rahman, Syarifah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using animated video learning media on the sciense learning outcomes of fourth-grade students at UPT SDN No. 78 Balang, Takalar Regency. This research employed a quantitative approach with a pre-experimental method using a One Group Pretest-Posttest Design. The population of this study consisted of all 43 fourth-grade students, and the entire population of this study consisted of all 43 fourth-grade students, and the entire population was used as the sample. Data collection techniques included learning outcome test (pre-test and post-test) and observation. The data were analyzed usinng descriptive statistical analysis and inferential statistical analysis through a paired sample t-test.The results showed that the mean pre-test score of students was 61,16, while the mean post-test score increased to 75, 93 after the implementation of animated video learnig media. This improvement indicates a change in students learning outcomes after the treatment was applied during the learning process. The t-test results revealed a t-value of -18,134 with a degree of freedom (df) of 42 and a significance value (sig. 2-tailed) of 0,001 <0,05. This indicates a significant difference between pre-test and post-test results.Therefore, it can be concluded that the use of animated video learning media has a possitive and significant effect on improving the science learnig outcomes of fourth-grade studentsat UPT SDN No. 78 Balang, Galesong Selatan District, Takalar Regency.